Peran Kepala Sekolah dalam Meningkatkan Kualitas Pendidikan Islam - Muhammad Fikri Hasbulloh; Opik Taufik Kurahman (STIKes Ibnu Sina Ajibarang, 2025)
The role of the principal is very significant in efforts to improve the quality of the institution he leads. In order to achieve this goal, the principal must carry out the role and function appropriately according to the needs. As a leader, the principal needs to understand what role needs to be carried out, be it as an educator, manager, administrator, supervisor, leader, innovator, or motivator. This study aims to identify the contribution of the principal in improving the quality of Islamic education. The method used is library research, which focuses on collecting, analyzing, and compiling information from various literature sources in order to gain an in-depth understanding of the topic being studied. The principal must have a high fighting spirit as an agent of change in an effort to improve the quality of education managed, the principal strives to achieve the predetermined quality standards. This effort can be realized through various strategic steps, such as making the right decisions, SWOT analysis, compiling quality improvement programs, implementing transparency, involving school residents and the community, effective budget management, and transformation towards a quality-conscious culture. Education itself is a process that aims to optimally develop all the abilities possessed by each student so that they can be used as capital to face various lives in the future.